Longitudinal Trajectories of Biomarkers of Kidney Tubular Function in Type 1 Diabetes - Christine P. Limonte; Xiaoyu Gao; Ionut Bebu; Jesse C. Seegmiller; Gayle M. Lorenzi; Bruce A. Perkins; Amy B. Karger; Valerie L. Arends; Andrew Paterson; Mark E. Molitch; Ian H. de Boer (Kidney International Reports)
Introduction: Tubular biomarkers may shed insight into progression of kidney tubulointerstitial pathology complementary to traditional measures of glomerular function and damage. Methods: We examined trajectories of tubular biomarkers in the Diabetes Control and Complications Trial and the Epidemiology of Diabetes Interventions and Complications Study (DCCT/EDIC Study) of type 1 diabetes (T1D). Biomarkers were measured in a subset of 220 participants across 7 time points over 26 years. Measurements included the following: kidney injury molecule 1 (KIM-1), soluble tumor necrosis factor 1 (sTNFR1) in serum or plasma, epidermal growth factor (EGF), monocyte chemoattractant protein-1 (MCP1) in timed urine, and a composite tubular secretion score. We described biomarker trajectories and examined how these were affected by intensive glucose-lowering therapy and glycemia. Results: At baseline, participants had a mean age of 28 years, 45% were women, and 50% were assigned to intensive glucose-lowering therapy. The mean estimated glomerular filtration rate (eGFR) was 125 ml/min per 1.73 m2 and 90% of participants had a urinary albumin excretion rate (AER) <30 mg/24h. Mean changes in biomarkers over time (percent/decade) were: KIM-1: 27.3% (95% confidence interval [CI]: 21.4–33.5), sTNFR1: 16.9% (14.5–19.3), MCP1: 18.4% (8.9–28.8), EGF: −13.5% (−16.7 to −10.1), EGF-MCP1 ratio: −26.9% (−32.2 to −21.3), and tubular secretion score −0.9% (−1.8 to 0.0), versus −12.0% (CI: −12.9 to −11.1) for eGFR and 10.9% (2.5–20.1) for AER. Intensive versus conventional glucose-lowering therapy was associated with slower increase in sTNFR1 (relative difference in change: 0.94 [0.90–0.98]). Higher HbA1c was associated with faster increases in sTNFR1 (relative difference in change: 1.06 per 1% higher HbA1c [1.05–1.08]) and KIM-1 (1.09 [1.05–1.14]). Conclusion: Among participants with T1D and normal eGFR at baseline, kidney tubular biomarkers changed significantly over long-term follow-up. Hyperglycemia was associated with larger increases in serum or plasma sTNFR1 and KIM-1, when followed-up longitudinally.